A role for tunneling nanotubes in virus spread - Lv, Weimiao; Li, Zichen; Wang, Shule; He, Jingyi; Zhang, Leiliang (Frontiers in Microbiology, 2024)
Tunneling nanotubes (TNTs) are actin-rich intercellular conduits that mediate distant cell-to-cell communication and enable the transfer of various cargos, including proteins, organelles, and virions. They play vital roles in both physiological and pathological processes. In this review, we focus on TNTs in different types of viruses, including retroviruses such as HIV, HTLV, influenza A, herpesvirus, paramyxovirus, alphavirus and SARS-CoV-2. We summarize the viral proteins responsible for inducing TNT formation and explore how these virus-induced TNTs facilitate intercellular communication, thereby promoting viral spread. Furthermore, we highlight other virus infections that can induce TNT-like structures, facilitating the dissemination of viruses. Moreover, TNTs promote intercellular spread of certain viruses even in the presence of neutralizing antibodies and antiviral drugs, posing significant challenges in combating viral infections. Understanding the mechanisms underlying viral spread via TNTs provides valuable insights into potential drug targets and contributes to the development of effective therapies for viral infections.